2021
DOI: 10.1186/s12880-021-00646-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the efficacy of tumor necrosis factor alpha antagonists in the treatment of Ankylosing spondylarthritis: a pilot study based on MR relaxometry technique

Abstract: Background SpA is a disease that seriously affects the quality of life and working ability of patients. At present, there is a lack of scientific and effective quantitative indicators to evaluate the activity of sacroilitis and the efficacy of tumor necrosis factor-α antagonists in the treatment of active sacroilitis. MRI STIR sequence is the most commonly used method for the diagnosis of sacroiliac joint inflammation, but its response to the disease still lags behind the pathological changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Dixon sequences can be performed with high spatial resolution, however, are less sensitive to the properties of the bone marrow compared to the other sequences that were discussed above [ 16 ]. Another investigation compared different mapping techniques and found that T1 mapping also allowed quantification of bone marrow oedema to assess the severity of inflammation and the treatment response [ 17 ]. Surprisingly, they proved T1 mapping to be superior, for that matter, to the other quantitative MRI techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Dixon sequences can be performed with high spatial resolution, however, are less sensitive to the properties of the bone marrow compared to the other sequences that were discussed above [ 16 ]. Another investigation compared different mapping techniques and found that T1 mapping also allowed quantification of bone marrow oedema to assess the severity of inflammation and the treatment response [ 17 ]. Surprisingly, they proved T1 mapping to be superior, for that matter, to the other quantitative MRI techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pilot study by Lin et al 41 compared different MR relaxometry techniques (T 1 mapping, T 2 mapping, T 2 * mapping) for mapping the subchondral bone marrow and demonstrated that these could be used to monitor response to TNF inhibitor treatment. Lin et al 41 found T 1 mapping had better diagnostic efficacy than T 2 mapping which was susceptible to confounding effects of the external environment including age, bone marrow composition, fat deposition and changes in the structure of bone trabeculae.…”
Section: Quantitative Mri Techniques and Biomarker Development In Axspamentioning
confidence: 99%
“…Magnetic relaxometry technique, detecting subtle changes of water content of the tissue, can quantitatively assess the extent of BME ( 15 , 16 ). Previous study showed that T1 mapping and T2* mapping values were effective quantitative indicators for clinical diagnosis, disease activity assessment and treatment monitoring in axSpA ( 17 ). However, due to the heterogeneity and the fluctuating nature of inflammatory activity in axSpA, relying solely on quantitative detection of BME is insufficient to evaluate the overall inflammatory activity level in axSpA patients ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%